2020
DOI: 10.1097/gox.0000000000003019
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Occipital Nerve Decompression Surgery in Migraine Headache

Abstract: Background: Migraine headache in the occipital region is characterized by a recurrent pain of moderate to severe intensity. However, the diagnosis can be difficult because of the multitude of symptoms overlapping with similar disorders and a pathophysiology that is not well-understood. For this reason, the medical management is often complex and ineffective. Methods: A literature search according to Preferred Reporting Items for Systematic Reviews and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 56 publications
1
9
0
Order By: Relevance
“…Our results agree with previous systematic reviews that support the effectiveness of migraine surgery for site IV. 14,19 In particular, our study observed that migraine surgery can be successful as early as 6 months compared to other trigger sites. Lee et al 32 conducted a retrospective study to evaluate whether removing the third occipital nerve, which is often encountered during the dissection for greater occipital nerve decompression, offers any additional benefit in surgical outcomes.…”
Section: Trigger Site IVmentioning
confidence: 63%
See 1 more Smart Citation
“…Our results agree with previous systematic reviews that support the effectiveness of migraine surgery for site IV. 14,19 In particular, our study observed that migraine surgery can be successful as early as 6 months compared to other trigger sites. Lee et al 32 conducted a retrospective study to evaluate whether removing the third occipital nerve, which is often encountered during the dissection for greater occipital nerve decompression, offers any additional benefit in surgical outcomes.…”
Section: Trigger Site IVmentioning
confidence: 63%
“…10,11 Deactivation of these peripheral trigger sites has been shown to improve symptoms. [12][13][14][15][16][17][18][19][20] Despite significant results after surgery, the differences in success rates and the subjective report of surgical outcomes in some studies have limited evaluation of its efficacy. Many of these patients undergo deactivation of nerves in multiple trigger sites; thus, determination of surgery success by specific trigger site has been difficult to report.…”
Section: Ementioning
confidence: 99%
“…Since Guyuron’s initial description, 1 numerous studies have been carried out around the world, unequivocally demonstrating the validity of this approach. 2–24 This approach is based on the neurolysis of extracranial nerves, which, when inflamed, act as trigger points and, as such, trigger headache attacks. Two of the nerves most frequently involved are the greater occipital nerve (GON) and lesser occipital nerve (LON).…”
Section: Techniquementioning
confidence: 99%
“…The aim of the decompression surgery of GON is to release potential compression points of GON and liberate the nerve (Bovim et al, 1992 ; Muehlberger, 2018 ). Knowing the anatomy and potential entrapment points of GON in detail is essential to achieve a successful decompression surgery (Baldelli et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%